2019
DOI: 10.4103/tjo.tjo_19_18
|View full text |Cite
|
Sign up to set email alerts
|

Semi-permanent smartphone adapter for microscopes: Design demonstration and workflow testing using a slit-lamp biomicroscope

Abstract: BACKGROUND: A smartphone microscope adapter is an alternative to a permanently mounted camera, which often requires a specially designed light path as well as a computer system for data storage and network connectivity. A common disadvantage of these adapters is that they need to be repeatedly mounted and dismounted; this is inconvenient during serial observations. PURPOSE: The study purpose is to develop and test a semi-permanent microscope adapter. METH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The use of a smartphone in the evaluation of the previous segment allows health professionals and even patients themselves to easily prepare photographs and videos of the eye records when the slit lamp is not available or to facilitate the examination of the eye structures or the presence of foreign bodies in the anterior chamber 14 . There are also devices that allow smartphones to be attached semi-permanently to the slit lamp, reducing assembly time in the case of concomitant use of these devices 15 .…”
Section: Anterior Segmentmentioning
confidence: 99%
“…The use of a smartphone in the evaluation of the previous segment allows health professionals and even patients themselves to easily prepare photographs and videos of the eye records when the slit lamp is not available or to facilitate the examination of the eye structures or the presence of foreign bodies in the anterior chamber 14 . There are also devices that allow smartphones to be attached semi-permanently to the slit lamp, reducing assembly time in the case of concomitant use of these devices 15 .…”
Section: Anterior Segmentmentioning
confidence: 99%
“…In other words, five magnifications can be realized in the design. from a smartphone with an SLM via a simple adapter in the eyepiece [13]. A common disadvantage of these adapters is that they need to be repeatedly mounted and dismounted, and this is inconvenient during serial observations.…”
Section: Design Principlementioning
confidence: 99%
“…The digital image is obtained from the SLM using a camera or smartphone by means of an adapter in the eyepiece [11][12][13][14]. C. Yen et al reported a method of image acquisition from a smartphone with an SLM via a simple adapter in the eyepiece [13]. A common disadvantage of these adapters is that they need to be repeatedly mounted and dismounted, and this is inconvenient during serial observations.…”
Section: Introductionmentioning
confidence: 99%